Variable Species Responses to Experimental Stony Coral Tissue Loss Disease (SCTLD) Exposure - Meiling, Sonora S.; Muller, Erinn M.; Lasseigne, Danielle; Rossin, Ashley; Veglia, Alex J.; MacKnight, Nicholas; Dimos, Bradford; Huntley, Naomi; Correa, Adrienne M. S.; Smith, Tyler Burton; Holstein, Daniel M.; Mydlarz, Laura D.; et al. (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) was initially documented in Florida in 2014 and outbreaks with similar characteristics have since appeared in disparate areas throughout the northern Caribbean, causing significant declines in coral communities. SCTLD is characterized by focal or multifocal lesions of denuded skeleton caused by rapid tissue loss and affects at least 22 reef-building species of Caribbean corals. A tissue-loss disease consistent with the case definition of SCTLD was first observed in the U.S. Virgin Islands (USVI) in January of 2019 off the south shore of St. Thomas at Flat Cay. The objective of the present study was to characterize species susceptibility to the disease present in St. Thomas in a controlled laboratory transmission experiment. Fragments of six species of corals (Colpophyllia natans, Montastraea cavernosa, Orbicella annularis, Porites astreoides, Pseudodiploria strigosa, and Siderastrea siderea) were simultaneously incubated with (but did not physically contact) SCTLD-affected colonies of Diploria labyrinthiformis and monitored for lesion appearance over an 8 day experimental period. Paired fragments from each corresponding coral genotype were equivalently exposed to apparently healthy colonies of D. labyrinthiformis to serve as controls; none of these fragments developed lesions throughout the experiment. When tissue-loss lesions appeared and progressed in a disease treatment, the affected coral fragment, and its corresponding control genet, were removed and preserved for future analysis. Based on measures including disease prevalence and incidence, relative risk of lesion development, and lesion progression rates, O. annularis, C. natans, and S. siderea showed the greatest susceptibility to SCTLD in the USVI. These species exhibited earlier average development of lesions, higher relative risk of lesion development, greater lesion prevalence, and faster lesion progression rates compared with the other species, some of which are considered to be more susceptible based on field observations (e.g., P. strigosa). The average transmission rate in the present study was comparable to tank studies in Florida, even though disease donor species differed. Our findings suggest that the tissue loss disease affecting reefs of the USVI has a similar epizootiology to that observed in other regions, particularly Florida.